Local infrastructure, resilience capacity and poverty in rural Southeast Asia - Tim Hartwig; Trung Thanh Nguyen (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2022)
We examine the association between infrastructure and a household's resilience capacity against shocks and the impacts of a household's resilience capacity on household consumption and poverty. We use panel data (collected in 2010, 2013, and 2016) from 1,698 households in Thailand and 1,701 households in Vietnam and employ an instrumental variable approach. We find that transportation and information and communication technology infrastructure help improve households' absorptive capacity in coping with shocks. Furthermore, this capacity can prevent households from reducing consumption and falling into poverty. Thus, rural development policies should attend to transportation and information and communication technology infrastructure.
Keywords: D01; O12; Q12; 330; Infrastructure; resilience capacity; poverty; instrumental variable; Thailand; Vietnam